Debatable questions of ways of commiting vandalism - Латиш, К. В. (Theory and practice of jurisprudence, 2016)
This article explores controversial issues of determining ways of committing vandalism, analyzes the contents of graffiti, using the precedents of the European Court of Human Rights.